Корекція гормонально-метаболічних порушень у дітей і підлітків з ожирінням - Маліновська, Т. М.; Большова, О. В. (Clinical Endocrinology and Endocrine Surgery, 2008)
The article is dedicated to the actual problem that is treatment of obesity in children and adolescents. 46 children aged 12-17 years (21 boy and 25 girls) were examined. The study of life history, an assessment of anthropometric parameters (the body mass, an index of body mass, a circumference of the waist and the femurs and also their correlation), an examination of total cholesterol, a lipid complex, fasting C-peptide, and standard glucose tolerance test were conducted in all the children. Disorders in carbohydrate metabolism were revealed in patients. A flat glycemic curve was noted in 36,9 % children. Increased C-peptide in blood, that is evidence of hyperinsulinemia, and dyslipidemic disorders were noted in this category of patients. Combined therapy (low-calorie diet and metphormin (Siophor, Berlin-Chemie) was used with a view to correct the exposed metabolic disorders in 19 children over 13 years. The use of preparation Siophor in children with abdominal obesity allows to a significant increase in the indices of lipid and carbohydrate metabolism in contrast to diet monotherapy.